The Specters of America. The Imperfect Construction of Americanness within the Performance of the Cultural Imaginary (KULT_online, 2014)
The Americanist Susanne Hamscha examines the performative character of American culture. Based on poststructuralist and cultural-theoretical considerations, she consults classic as well as contemporary texts regarding the interplay of performance and the cultural imaginary in the construction of 'America' and 'Americanness'. She focuses precisely on those moments in which the ostensibly smooth production of dominant imaginations is disrupted by their inherent subtexts. As a result, numerous moments of resistance manifest within the hegemonic American culture which counteract the sheer reproduction of the norm.